2004
DOI: 10.1023/b:inrt.0000009445.19495.46
|View full text |Cite
|
Sign up to set email alerts
|

Combination Approaches for Multilingual Text Retrieval

Abstract: We describe the Eurospider component for Cross-Language Information Retrieval (CLIR) that has been employed for experiments at all three CLEF campaigns to date. The central aspect of our efforts is the use of combination approaches, effectively combining multiple language pairs, translation resources and translation methods into one multilingual retrieval system. We discuss the implications of building a system that allows flexible combination, give details of the various translation resources and methods, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
3
31
0
2
Order By: Relevance
“…McCarley [28] trained a statistical MT system from a parallel corpus, applied it to perform QT and DT, and showed that the combination of scores from QT and DT drastically improved either method alone. Similar results have been reported using either a full-fledged MT system [4] or a simple translation algorithm [7]. Kraaij et al [19] used the translation model of IBM Model 1 [5], obtained from an automatically constructed parallel corpus from the web, and also reported that the combination of QT and DT improved either method alone.…”
Section: Cross-lingual Retrievalsupporting
confidence: 70%
See 2 more Smart Citations
“…McCarley [28] trained a statistical MT system from a parallel corpus, applied it to perform QT and DT, and showed that the combination of scores from QT and DT drastically improved either method alone. Similar results have been reported using either a full-fledged MT system [4] or a simple translation algorithm [7]. Kraaij et al [19] used the translation model of IBM Model 1 [5], obtained from an automatically constructed parallel corpus from the web, and also reported that the combination of QT and DT improved either method alone.…”
Section: Cross-lingual Retrievalsupporting
confidence: 70%
“…For Chinese translation representation, different values of μ were used for P (w|d) and P (d|q) of Eq. (11), by fixing to 0 and 4 The smoothing parameter μ at the second retrieval was fixed to 1,500 for both representations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining the two ranked lists yielded better MAP than when either approach was used alone. Similar improvements have since been reported by others using variants of that technique (Braschler, 2004;Kang et al, 2004). Boughanem et al (2001) tried one way of pushing this insight inside the retrieval system, simply filtering out potentially problematic translations that were attested in only one direction.…”
Section: Bidirectional Translationmentioning
confidence: 60%
“…Ces ressources linguistiques ont chacune démontré leurs forces et leurs faiblesses. Or, il semble que la démarche la plus prometteuse consiste à combiner plusieurs ressources différentes pour la traduction (Braschler 2004).…”
Section: La Recherche D'information Multilingue (Riml)unclassified